2011
DOI: 10.5251/abjna.2011.2.1.74.79
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of rate and time of application of rice-husk powder as an organic amendment on cowpea (Vigna unguiculata L.,walp) inoculated with cowpea mottle virus

Abstract: A Screen house experiment using potted plants was carried out to assess the effects of time and rate of application of Rice-husk powder as an organic amendment on cowpea (Vigna unguiculata L Walp) cv. Ife Bimpe, that were mechanically inoculated with Cowpea Mottle Virus (CM e V). The results showed that the organic amendment was very effective on plants with soils amended with rice-husk powder, as the plants exhibited better yields and productivity. The amended plants also showed considerable less susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The lack of difference may be attributed to the fact that production of dry matter which directly associated with growth did not pick up. This is in full agreement with the findings of Aliyu et al, (2011) that at the second week, plant heights were not significantly affected by rate of application of the amendment. However, the non-significant (P<0.05) effects on stem diameter and number of leaves were perhaps due to gradual increase in such parameters in relation to the rice-husk incorporation period.…”
Section: Results and Discussion Soil Propertiessupporting
confidence: 92%
“…The lack of difference may be attributed to the fact that production of dry matter which directly associated with growth did not pick up. This is in full agreement with the findings of Aliyu et al, (2011) that at the second week, plant heights were not significantly affected by rate of application of the amendment. However, the non-significant (P<0.05) effects on stem diameter and number of leaves were perhaps due to gradual increase in such parameters in relation to the rice-husk incorporation period.…”
Section: Results and Discussion Soil Propertiessupporting
confidence: 92%
“…Sangar et al, (1982), had reported that Azadirachta indica possessed some antiviral compounds active against plant pathogenic viruses, these antiviral compounds are grouped as furocoumarins, alkaloids, terpenoids, lignins, and specific proteins (Zipf 1995). The use of botanicals (rice-husk powder), as an organic amendment to suppress cowpea mottle virus in cowpea had been reported by Aliyu et al,( 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Muhammed et al (2001) in their studies observed that rice product like rice husks composted soil reduced the incidence of wilting of P. biglobosa caused by F. solani. According to Aliyu et al (2011) amending cowpea with rice husk showed considerable less susceptibility to the virus pathogen infecting cowpea compared to the nonamended plants. He further showed that the rate and time of application of the Rice-husk powder was a key factor in the ameliorative effect of this organic amendment in the suppression of the viral inoculums.…”
Section: The Effects Of Mango Leaves Ash and Rice Chaff On Isolated mentioning
confidence: 99%